Analysis of Academic Experiences in University Students: QVA and QVA-r Systematic Review - Correa-Aranguren, Iris Gladys (2024)
A systematic review of the literature was carried out with the aim of analyzing existing research on the academic adjustment of university students, focusing on the application of the QVA and QVA-r instruments. The review covered studies published between 1995 and 2023, consulting databases such as Scopus, Redalyc and SciELO. The methodology followed the PRISMA Protocol and resulted in the selection and analysis of 39 studies. The findings showed a significant concentration of research in Brazil (69.23%), followed by Portugal (15.38%). Most studies were conducted between 2015 and 2018 (30.77%). The number of authors varied, with most involving three authors per publication (33.33%). The review highlighted the relationship between academic expectations and college adjustment, the importance of resilience in challenging contexts, the significant role of extracurricular activities, and the intricate connection between stress and academic adjustment. Despite the wealth of literature reviewed, the lack of evidence in psychometric studies of the QVA and QVA-r was noted, highlighting the need for future research to delve deeper into the validation and application of these instruments in different cultural and linguistic contexts. This study provides a comprehensive overview of existing research on academic adjustment, identifying key themes and areas of opportunity for future research.